On the elicitation and measurement of betrayal aversion - Simone Quercia (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2015)
Betrayal aversion has been operationalized as the evidence that subjects demand a higher risk premium to take social risks compared to natural risks. This evidence has been first shown by Bohnet and Zeckhauser (2004) using an adaptation of the Becker-DeGroot-Marshak mechanism (BDM, Becker et al. (1964)). We compare their implementation of the BDM mechanism with a new version designed to facilitate subjects' comprehension. We find that, although the two versions produce different distributions of values, the size of betrayal aversion, measured as an average treatment difference between social and natural risk settings, is not different across the two versions. We further show that our implementation is preferable to use in practice as it reduces substantially subjects' mistakes and hence the likelihood of noisy valuations.
Keywords: C90; D81; 330; experiments; betrayal aversion; trust game; Becker-DeGroot-Marshak mechanism; preference elicitation